Evaluating the ParticipACTION "Think Again" Campaign. (August 2016) - Gainforth, Heather L.; Jarvis, Jocelyn W.; Berry, Tanya R.; Chulak-Bozzer, Tala; Deshpande, Sameer; Faulkner, Guy; Rhodes, Ryan E.; Spence, John C.; Tremblay, Mark S.; Latimer-Cheung, Amy E.
Introduction . ParticipACTION's 2011 "Think Again" campaign aimed to draw parents', and specifically mothers', attention to the amount of physical activity (PA) their children do relative to the national guidelines (physical activity guidelines [PAG]). Purpose . To evaluate ParticipACTION's "Think Again" campaign in the context of the hierarchy of effects model. Methods . Data were drawn from "Think Again" campaign evaluations conducted among two cohorts of parents with children ages 5 to 11 years (3 months postcampaign launch [T1], n = 702; 15 months postlaunch [T2], n = 670). Results . At T2, campaign awareness was weakly associated with parents agreeing that their children were not active enough ( p = .01, d = .18). Parents who were aware of the campaign showed greater knowledge of PAG ( p s < .01, ϕs > .14), had higher outcome expectations about their children engaging in PA ( p < .01, d = .16), had stronger intentions to help their child meet the guidelines ( p < .01, d = .18), and engaged in more parental support behaviors ( p < .001, d = .31) as compared with parents who were not aware. At T1, parents aware of the campaign had greater perceived behavioral control (PBC) to influence their child's PA participation ( p < .01, d = .22), whereas parents not aware of the campaign had greater PBC to find practical ways to help their child be active ( p < .01, d = .26). Parental awareness of the campaign was not associated with children meeting the PAG at either time point ( p s > .05). Conclusions . The campaign appeared marginally effective for increasing parental knowledge of PAG and for creating realistic awareness of children's PA levels. Additional intervention strategies are needed to produce larger effects and to change parental behavior.